The future direction of cyberology - Ahamad Tarmizi Azizan; Ahmad Rasdan Ismail; Nik Zulkarnaen Khidzir; Zukeri Ibrahim; Tenh Hock Kuan; Mohamad Shahfik Afendi Abdul Ghani; Mohd Hafiz Faizal Mohamad Kamil (Universiti Malaysia Kelantan, 2014)
The objective of this review paper is to discuss the future direction of cyberology. It consists of seven main parts. Part 1 of this review focused on future direction of infographics. Part 2 of this review presents the future study of software engineering. Part 3 explores the future of digital storytelling. Part 4 shows the future trends in computer generated imagery. Part 5 discovers future potential of mobile games. Part 6 reveals the future development of intelligent tutoring systems. Lastly, Part 7 discusses the future research of human computer interaction.